Efficacy and Safety of Netakimab, A Novel Anti-IL-17 Monoclonal Antibody, in Patients with Moderate to Severe Plaque Psoriasis. Results of A 54-Week Randomized Double-Blind Placebo-Controlled PLANETA Clinical Trial - Puig, Luís; Bakulev, Andrey L.; Kokhan, Muza M.; Samtsov, Alexey V.; Khairutdinov, Vladislav R.; Morozova, Maria A.; Zolkin, Nikita A.; Kuryshev, Ivan V.; Petrov, Alexey N.; Artemeva, Antonina V.; Zinkina-Orikhan, Arina V. (Dermatology and therapy, 2021)
Introduction Netakimab (NTK), an original humanized anti-interleukin-17 monoclonal antibody, showed therapeutic efficacy in moderate-to-severe plaque psoriasis in a phase 2 clinical study. Herein we report the results of 54 weeks of a phase 3 PLANETA trial aimed to evaluate the efficacy and safety of two NTK regimens vs. placebo. Methods Two hundred thirteen patients with moderate-to-severe plaque psoriasis were randomly assigned to receive NTK 120 mg once every 2 weeks (NTK Q2W), NTK 120 mg once every 4 weeks (NTK Q4W) or placebo. During the first 3 weeks, patients received subcutaneous injections of NTK or placebo (according to the allocation) once a week. Patients in the NTK Q2W group then received NTK at weeks 4, 6, 8 and 10. Subjects in the NTK Q4W group received NTK at weeks 6 and 10 and placebo at weeks 4 and 8. Patients in the placebo group received placebo injections at weeks 4, 6, 8 and 10. Treatment was unblinded at week 12. During the open-label phase, patients in both NTK groups continued to receive NTK Q4W. The primary efficacy endpoint was the proportion of patients in each group who achieved a ≥ 75% reduction from baseline in psoriasis area and severity index (PASI 75) at week 12. Results A total of 77.7%, 83.3% and 0% of patients had a PASI 75 response at week 12 in the NTK Q2W, NTK Q4W and placebo groups, respectively ( P < 0.0001, Fisher’s exact test, ITT). The effect was maintained throughout the 1-year treatment. NTK showed a good safety profile and low immunogenicity. Conclusion Treatment with NTK results in high rates of sustained clinical response in patients with moderate-to-severe plaque psoriasis. The study is ongoing; thus, long-term use efficacy and safety data are forthcoming. Clinical Trial Registration The trial is registered at the US National Institutes of Health (ClinicalTrials.gov; NCT03390101).